Asuhan Keperawatan Anak Pada Pasien Dengan Asma Bronkial Di Ruang Anak RSUD Prof. H. Muhammad Yamin, SH Pariaman Tahun 2026 - Viyona Martisa Putri; Prima Yoselina; Reska Handayani; Erpita Yanti (CV. ITTC INDONESIA, 2026)
Bronchial asthma is a global health problem that occurs in both developed and developing countries and is widely known in the community. Based on data from the pediatric ward of Prof. H. Muhammad Yamin, SH Pariaman Regional General Hospital for the period January 2023–December 2025, there were 131 cases of bronchial asthma. This study aims to provide care for children with bronchial asthma using the research method used, namely a case study through the bleeding process: assessment, diagnosis, intervention, implementation, and evaluation, which was carried out on February 18–22, 2026. The results of the study showed four causative problems, namely ineffective breathing patterns, ineffective airway clearance, hyperthermia, and nutritional deficits. Interventions provided included effective coughing exercises, airway management, hyperthermia management, and nutritional management. After treatment, the patient's condition improved, marked by reduced shortness of breath and a decrease in body temperature on the 4th and 5th days, but the problem of nutritional deficits was not resolved by the 5th day. This study emphasizes the importance of parents' role in supporting their child's recovery, including recognizing early signs of asthma, providing treatment during an attack, and preventing relapses. Initial treatment includes calming the child, maintaining a sitting position, using an inhaler or nebulizer, and avoiding triggers. Appropriate prevention and management can reduce asthma relapses in children.